FIRM VALUE: PRICE EARNING GROWTH DETERMINATION IN AGRICULTURAL SECTOR COMPANIES - Jamaludin, Ali; Purwanto, Budi; Ermawati, Wita Juwita (Universitas Brawijaya, Indonesia, 2021)
This study analyzes firm value with several variables that determine the high and low firm value. The ratios used in measuring firm value are price earnings growth (PEG) and price-earnings ratio (PER). In addition, in this study, PER served as a mediating variable and a comparison PEG in describing a true firm value. The samples obtained were 17 agricultural sector companies listed on the IDX for five years of observation from 2015 to 2019. The analytical methods used were RMSE, panel data regression, and path analysis. This research found that PEG is better at describing a firm's true value than PER. In addition, this study also found that the variable current ratio and debt to total capitalization ratio do not affect PEG. Meanwhile, the variable return on equity affects PEG. Next, the variable current ratio, debt to total capitalization ratio, and return on equity affect PEG after being mediated through PER. The return on equity is the determining variable in influencing the high and low PEG values. Further PEG research can be carried out on companies with high-risk characteristics such as banking, mining, property, real estate, construction, and buildings.